The result of modified hydrothermal nanotitania extract to the Escherichia coli growth - Ahmad Mukifza Harun; Nor Farid Mohd Noor; Mohamad EzanyYusof; Razif Abas; Mohammad Khursheed Alam (2020)
Background: This research was planned to search for a potential of modified hydrothermal nanotitania extract in inhibiting the growth of bacteria commonly known in medical field. It is also aims to test this substance against common medical bacteria,Escherichia coli. Materials and methods: In this test, suspension of modified hydrothermal nanotitania extract (together with 0.01%, 0.03% and 0.05% silver) and undoping (positive control contains TiO2 and no silver) were prepared by mixing of TiO2 in Mueller Hinton Broth (MH) agar. The platecontaining the bacteria and TiO2 were observed after 24 hour, 48 hours and 72 hours incubation at 37o C for any growth of bacteria. Results: There was no growth of Escherichia coliin the plates containing the bacteria and modified hydrothermal nanotitania extract except in the control media. Conclusions: The finding suggested the modified hydrothermal nanotitania extractioninterfered the growth of Escherichia coli.